Physical Training Assistance for Prospective Official School Students at Jasdam II/Sriwijaya - Ferdy Yangkara, Yosef; Taroreh, Bangkit Seandi (PT FORMOSA CENDEKIA GLOBAL, 2023)
Community service aims to increase physical training knowledge of prospective official school students at Jasdam II/Sriwijaya. This community service activity entitled physical training assistance for prospective official school students at Jasdam II/Sriwijaya is really needed because it is one of the efforts aimed at increasing the knowledge of physical training for prospective official school students at Jasdam II/Sriwijaya. Implementation of community service activities uses the mentoring method with the following sequence of implementation: 1) planning, 2) implementation, 3) evaluation. Collecting community service data uses a questionnaire with 10 questions with quantitative data analysis. The subjects of community service are 40 prospective service students. The result of community service is an increase in knowledge about physical training for prospective service students by 100% (40 people) while the implementation of the results of service, namely physical training activities for prospective service school students at Jasdam II/Sriwijaya, continues to be carried out.